How Psychological Empowerment Influences Faculty Members’ Change Orientation: Does Knowledge Inertia Have a Mediating Role? - Alanoglu, Muslim; Karabatak, Songül (Universitepark, 2023)
Background/purpose – This study aims to determine the effect of faculty members’ psychological empowerment on their change orientation and the mediating role of knowledge inertia (learning and experience) in this effect. Materials/methods – A cross-sectional research design was used to achieve this goal. The opinions of 398 faculty members working in six universities in Türkiye were collected via the survey method. Results – The results showed that the faculty members’ psychological empowerment had a favorable effect on their levels of change orientation and a negative effect on their levels of learning inertia. Additionally, it was shown that the faculty members’ psychological empowerment had little effect on their experiential inertia. Additionally, there was no discernible relationship between degrees of faculty members’ change orientation and perceived knowledge inertia (learning and experience). Conclusion – The study’s results imply that faculty members who see their jobs as meaningful have sufficient knowledge about their jobs, are responsible for making decisions about their jobs, and accept change easily. It was also concluded that these faculty members have high levels of change orientation. © 2023 by the author(s).
Keywords: change orientation; faculty member; knowledge inertia; psychological empowerment